2016
DOI: 10.1002/cam4.858
|View full text |Cite
|
Sign up to set email alerts
|

The histological characteristics and clinical outcomes of lung cancer in patients with combined pulmonary fibrosis and emphysema

Abstract: Combined pulmonary fibrosis and emphysema (CPFE) is an important risk factor for lung cancer (LC), because most patients with CPFE are smokers. However, the histological characteristics of LC in patients with CPFE (LC‐CPFE) remain unclear. We conducted this study to explore the clinicopathological characteristics of LC‐CPFE. We retrospectively reviewed data from 985 patients who underwent resection for primary LC, and compared the clinicopathological characteristics of patients with LC‐CPFE and non‐CPFE LC. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Several previous studies showed lung cancer in patients with CPFE was advanced stage (10,14), while other studies indicated that more lung cancer patients with CPFE were early stage (11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22). Pulmonary function test was conducted in several studies, and the results have varied (11)(12)(14)(15)(16)(17)(18)(19)(20)(21)(22). CPFE was an independent factor for a poor prognosis in lung cancer patient with CPFE (11,18,21).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Several previous studies showed lung cancer in patients with CPFE was advanced stage (10,14), while other studies indicated that more lung cancer patients with CPFE were early stage (11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22). Pulmonary function test was conducted in several studies, and the results have varied (11)(12)(14)(15)(16)(17)(18)(19)(20)(21)(22). CPFE was an independent factor for a poor prognosis in lung cancer patient with CPFE (11,18,21).…”
Section: Introductionmentioning
confidence: 96%
“…In three previous studies of lung cancer patients with CPFE adenocarcinoma was the most common type of cancer, followed by squamous cell carcinoma (10)(11)(12). However, other studies had shown that squamous cell carcinoma was the most common type of cancer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several previous studies showed lung cancer in patients with CPFE was advanced stage (10,14), while other studies indicated that more lung cancer patients with CPFE were early stage (11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations